THE EFFECT OF SELF-ESTEEM IN ORGANIZATION AND SELF-AWARENESS ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE IN ASTRA CREDIT COMPANIES MEDAN BRANCH - Indah Permata Sembiring; Ritha F Dalimunthe; Parapat Gultom (CV. Radja Publika, 2023)
In facing competition in the global era, finance companies are required to work more efficiently and effectively. An efficient company must be able to run a business with targets that can be achieved according to company goals. Therefore, companies must have human resources or what are called employees, people who are commonly called employees to carry out household activities of the company's production so that the company generates maximum profits. Therefore employees are the most important element to achieve company goals. Employees must also be able to carry out the tasks determined by the company. Employee ability is reflected in performance, good performance is optimal performance. The purpose of this study was to find out how the influence of self-esteem in an organizational context, self-awareness on employee performance with organizational commitment as a mediating variable at Astra Credit Companies (ACC) Medan Branch. This type of research is associative research with a quantitative approach with a sample of 85 respondents. The data analysis technique uses structural equation modeling (SEM) with the Smart PLS version 3.0 analysis tool. The results showed that self-esteem in the organization had a positive and significant effect on employee performance, self-awareness had a positive and significant effect on employee performance, self-esteem in the organization had a positive and significant effect on organizational commitment, self-awareness had a positive and significant effect on organizational commitment, and organizational commitment organization has a positive and significant effect on employee performance. Then the results of the tests conducted show that work organizational commitment is able to mediate the relationship between self-esteem in the organization and employee performance, and organizational commitment is able to mediate the relationship between self-awareness and employee performance.